Pharmacogenetics of Clopidogrel - A O'Connor, Stephen; Hulot, Jean-Sebastien; Silvain, Johanne; Cayla, Guillaume; Montalescot, Gilles; Collet, Jean-Philippe (Current Pharmaceutical Design, 2012)
Clopidogrel used in conjunction with aspirin has a central role in the treatment of patients with an acute coronary syndrome (ACS) and/or undergoing percutaneous coronary intervention (PCI). The pharmacokinetic and pharmacodynamic responses to this drug are highly variable leaving up to one third of patients with inadequate platelet inhibition or high on-treatment platelet reactivity (HPR), and subsequent increased ischemic cardiovascular events. Genetic variability in drug absorption and metabolism is a key factor responsible for the inefficient generation of the active drug metabolite. The two-step hepatic cytochrome P450 (CYP)-dependant oxidative metabolism of the prodrug appears to be of particular importance. Pharmacogenomic analyses have identified loss-of-function variant alleles of CYP 2C19 and specifically the 2C19*2 allele, to be the predominant genetic mediators of the antiplatelet effect of clopidogrel. Carriers were have been shown to have lower active metabolite levels of clopidogrel, higher platelet reactivity and associated poorer outcomes. Rapid and accurate point-of-care genetic tests to identify these alleles are currently in development but several questions about the role of such testing remain such as patient selection and whether personalized treatment based on genotype has a positive impact on clinical outcome. At present, genetic testing cannot be recommended in routine clinical practice due to insufficient prospective data. However, the significant body of research published to date suggests a likely role when used in combination with platelet function analysis in ACS patients undergoing stenting who have other known risk factors for recurrent ischemic events.
Keywords: thrombosis